Peningkatan Keterampilan Berbicara Menggunakan Metode Role Playing pada Siswa Kelas III-B MIN 8 Gunungkidul - Rujati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
The purpose of this study is to improve the quality of the process and results of speaking skills by using the role-playing method for third-grade students. MIN 8 Gunungkidul 2018/2019 Academic Year. This research is in the form of Classroom Action Research (CAR). The subject of this study was class III. B MIN 8 Gunungkidul 2018/2019 Academic Year amounted to 21 students. Data collection techniques used were observation, interviews, tests, and document studies - data validity using source triangulation and method triangulation. The data analysis technique used is an interactive analysis model, including data reduction, data presentation, and drawing conclusions or verification. The research process was carried out in two cycles. Each cycle consists of four stages, namely: (1) action planning, (2) implementation of actions, (3) observation, and (4) reflection. Based on the results of the study, it was concluded that the role-playing method could improve the quality of the process and the results of speaking skills in class III students. B MIN 8 Gunungkidul Academic Year 2018/2019. This can be proven by the increasing percentage of students' attitudes to aspects of interest, activity, cooperation, and seriousness in the first cycle and second cycle. In the first cycle, the classic percentage of students' attitudes is 77.77% interest, 66.66% student activity, 72.22% cooperation, and 50% seriousness. In the second cycle, the classic percentage of a student, attitudes increased to interest 88.88%, student activity 77.77%, cooperation 83.33%, and sincerity 77.77%. The quality of the results is proven by obtaining the average value of the initial test results before the action (pra siklus), which is 68.77 with classical completeness of 27.77%. In the first cycle, the grade average value increased to 73.44 with 61.11% classical completeness. After the action in the second cycle, the average grade value increased to 80.77 with classical completeness 88.88%.